THE IMPORTANCE Of INNOVATIVE DEVELOPMENT OF SMALL AND MEDIUM BUSINESS (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
The article examines the conditions and features of the use of simulation innovation in small and medium-sized businesses (SMEs) in Uzbekistan. Indicators of the level of economic development of the regions are indicated.